A novel lutetium(III) acetate phthalocyanine directly substituted with N, N'-dimethylaminophenyl groups via CC bonds and its water-soluble derivative for photodynamic therapy. Issue 7 (15th February 2017) - Al-Raqa, Shaya Y.; Köksoy, Baybars; Durmuş, Mahmut
Graphical abstract: Highlights: Synthesis of a N, N ′-dimethylaminophenyl substituted lutetium(III) phthalocyanine. Synthesis of a quaternized, water soluble lutetium(III) phthalocyanine. Photochemical properties of the phthalocyanines in both DMSO and water. High singlet oxygen generation for potential photodynamic therapy of cancer. Abstract: In this study, the novel 4-( N, N′ -dimethylamino)phenyl substituted lutetium(III) acetate phthalocyanine (2 ) and its quaternized derivative (3 ) were synthesized via a Suzuki-Miyaura coupling reaction between tetrakis(iodo) lutetium(III)acetate phthalocyanine (1 ) and 4-( N, N -dimethylamino)phenylboronic acid, and subsequent quaternization using dimethyl sulfate, respectively. The obtained phthalocyanine3 exhibited excellent solubility in water which is important for photodynamic therapy applications. Photophysical properties such as fluorescence quantum yield and fluorescence lifetime, and photochemical properties such as singlet oxygen generation and photostability were investigated to determine their suitability for photodynamic therapy. The lutetium(III) phthalocyanines, especially quaternized derivative3, showed promising properties as potential photosensitizers for the treatment of cancer, producing higher singlet oxygen (ΦΔ  = 0.59) than motexafin lutetium (ΦΔ  = 0.31) which is a clinically used lutetium texaphyrin photosensitizer.